Applying Knowledge Management to Web-Based Courses Development - Xuesong, Yang (2010)
Web-based course, as a carrier of network education, is a key element determining the quality of network education, and it plays an increasingly prominent role in the network education. Applying Knowledge management to web-based courses is a new area of research in recent years, and knowledge management provides a new perspective and new idea for the design and development of web-based courses. Web-based courses based on knowledge management focus on knowledge acquisition, sharing and exchange and emphasize the transfer of explicit knowledge and tacit knowledge, and eventually reach the knowledge innovation. The aim of this research is to apply the theories, methods and technologies of knowledge management to the design and development of web-based courses, and to foster learners' ability of knowledge management. Knowledge management theory plays an important role in guiding the development and construction and improving qualities of web-based courses. This research uses the document research method, consulting a number of periodicals and books, and collects a large number of related papers, including the basic issues on knowledge management, such as its connotation and extension, knowledge transformation, knowledge management strategy, facilities and so on. In addition, this research brings forward the basic design principles, strategies, web-based course design process model and web-based course system frame model based on knowledge management. A web-based course prototype called "Advanced Programming JAVA" was developed to evaluate the second model.